Salivary Cortisol Levels and Burning Symptoms in Patients with Burning Mouth Syndrome before and after Low Level Laser Therapy: a Double Blind Controlled Randomized Clinical Trial - Ivana Škrinjar; Božana Lončar Brzak; Valentina Vidranski; Vanja Vučićević Boras; Ana Andabak Rogulj; Božidar Pavelić (Acta Stomatologica Croatica, 2020)

(untitled)
Objectives: Burning mouth syndrome (BMS) is a disorder which is described as burning sensation of the oral mucosa without pathological changes. Most of the patients have some underlying stressful conditions. Stress induces an increase in secretion of different endocrine glands resulting in higher levels of glucocorticoids. One of the options for treatment of BMS includes low level laser therapy (LLLT). The aim of this research was to determine salivary cortisol levels and intensity of burning symptoms in BMS patients before and after LLLT. Material and Methods: Twenty-three participants were allocated by randomization in two groups: 12 patients in the study group and 11 patients in the placebo group. Cortisol levels in all patients were analyzed from the sample of saliva collected without stimulation. In both groups, the LLLT was performed once a day for ten consecutive days (excluding weekend) with Ga-Al-As light-emitting diode type of laser, with a wavelength of 685nm. In the control group, LLLT was done with inactive laser probe which was only emitting audio signal. The intensity of burning symptoms was measured by a visual analogue scale (VAS). The VAS and unstimulated saliva were measured at baseline and on the last day of the LLLT. A quantitative analysis of saliva was performed using competitive commercial ELISA-kit. Results: VAS scores and salivary cortisol levels were significantly lower in both groups after LLLT. Conclusions: LLLT can be useful in patients with BMS for reducing burning symptoms and salivary cortisol level. Future studies on a larger number of patients should clarify whether the positive results are an outcome of laser effectiveness or of placebo effect.